ANALYSIS OF THE ARABIC LANGUAGE ENVIRONMENT AT THE AL-NOOR INSTITUTE IN PADANGSIDEMPUAN: TAHLILU BIATI AL-LUGHOH AL-ARABIYAH BI MA’HAD AN-NUR PADANG SIDIMPUAN - Muhammad Firdaus Lubis; Sopian Sinaga; Fian Triadi (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2025)
The researcher was intrigued by the development of the Arabic language environment at An-Nur Institute, Padangsidimpuan, particularly between 2013 and 2016, when a dynamic Arabic-speaking atmosphere emerged. This environment resulted fromemotional, physical, and intellectual efforts by teachers and supervisors who implemented systems, regulations, and language programs. However, despite these efforts, students still do not consistently use Arabic daily, revealing a gap between the intended environment and actual practice. This study aims to analyze the Arabic language environment at An-Nur Institute and identify its supporting and hindering factors. Using a qualitative descriptive method with a case study design, data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive qualitative analysis model (data reduction, data display, and conclusion drawing). The findings reveal that although supporting factors such as location, digital applications, and qualified teachers exist, the absence of a unified strategy, standards of proficiency, and consistent monitoring has hindered the effectiveness of the Arabic language environment.